The pathogenic and antimicrobial characteristics of an emerging Streptococcus agalactiae serotype IX in Tilapia. (September 2018) - Zhang, Ze; Lan, Jiangfeng; Li, Yuhui; Hu, Minqiang; Yu, Angen; Zhang, Jie; Wei, Shun
Abstract: Streptococcus agalactiae ( S. agalactiae, GBS) infection has caused significant economic loss in the tilapia aquaculture, which is one of the most important commercial fish worldwide. Among the 10 serotypes of GBS, serotypes Ia, Ib, II and III were epidemic in tilapia while serotype IX has never been found in tilapia before. In this study, 80 strains isolated from moribund tilapia in China were identified as GBS. All the isolates have been classified as serotype III or serotype IX of GBS. Unexpectedly, the serotype IX has never been reported in fish, but it was epidemic in mammals. Antimicrobial resistance results showed that serotype IX but not III was resistant to streptomycin and erythromycin. Artificial infection results showed that both serotypes could cause serious pathological injuries in the infected tissues of tilapia. Furthermore, serotype IX instead of serotype III, mainly infected the brain of tilapia. The results will shed a new light on the epidemic and pathogenicity of GBS, and will pave a new way for the prevention of Streptococcosis in tilapia. Highlights: Serotype IX as an emerging serotype of GBS from the cultured tilapia in China has been identified. Serotype IX but not III was resistant to streptomycin and erythromycin. Serotype IX instead of serotype III, mainly infected the brain of tilapia.